Researching anxiety of pre-service teachers in teaching science and mathematics program - Veena Prachagool; Prasart Nuangchalerm; Juhji Juhji; Thanapol Thavornsil (Intelektual Pustaka Media Utama, 2021)
This study purposed to investigate researching anxiety of pre-service teachers that might want to explain why they are able to learn successfully in the context of difference in program of study. There were 15 pre-service teachers in M.Ed. program of teaching science and mathematics voluntary participated. Learning Anxiety Questionnaire (LAQ) was employed their anxiety towards learning through Google Form. The study revealed that pre-service teachers had anxiety at medium level. However, some of item present they had different level of anxiety. The effective learning for decreasing level anxiety needs to be more discussed.